Whole-Buildings Life Cycle Assessment Sensitivity to Scenario Choices. (June 2019) - Guimarães, G D; Zucarato, L; Saade, M; Silva, M; Silva, V G
Abstract: Life cycle assessment (LCA) is an important technique to measure environmental impacts of products and processes and its application to diagnose and optimize whole-buildings' environmental performance has increased in the past years. However, LCA results carry uncertainties which may limit their utility as environmental decision-making support. Since normative choices are unavoidable within whole-building LCA (wbLCA) modelling, it becomes important to analyse their inherent uncertainty. Recent literature indicates that different material wastage values, lifetime choices and end of life scenarios are the main uncertainties drivers on wbLCA. To understand how these choices influence wbLCA results, we conducted a scenario analysis, to estimate the effects that parameters and input choices produce on final results by describing possible future situations. Cumulative Energy Demand (CED) and CML 2001 v.2.05 methods were selected for calculating embodied energy and global warming potential in SimaPro 7.3. Our results indicate that wbLCA outcomes vary greatly with different alternatives for normative choices, and a scenario uncertainty analysis is necessary to understand all implications of its results.